The Influence of Infographic Media Education of Earthquake Disaster Evacuation System on The Attitude of Unisa Security Team. - Rhida Millyana Faaroek; Muhaji; Ellyda Septiani Pramita (Journal of Indonesian Anesthesiology Nursing, 2025)
Background: Indonesia frequently faces earthquakes due to its geographical position, with Yogyakarta being one of the vulnerable regions. Universitas 'Aisyiyah Yogyakarta is located in a high-risk location. The attitude of the security staff in managing emergency situations is crucial. Consequently, education through video infographic media on the earthquakes disaster evacuation method is necessary for enhancing attitudes towards managing emergency situations. Methods: The study employed a pre-experimental design with a one-group pre-test post-test design, involving a population of 35 personnel from the UNISA security team. Data were obtained using the total sampling method through an attitude questionnaire administered before and after the intervention involving instructive video infographics on the earthquakes disaster evacuation system. Results: The study's results showed that the majority of pretest attitudes were positive, with 31 respondents (88.6%), whereas posttest attitudes were very positive, with 33 respondents (94.3%). The Wilcoxon test obtained a significance value (2-tailed) of 0.000 between variable X and variable Y (p < 0.05). Conclusion: Further research with larger sample sizes is required to evaluate the long-term efficacy of infographic media education programmes.